Parasite in the Mackerel (Rastrelliger sp.) Landed in the Atapupu TPI - Andiewati, Suci; Turnip, Gilbert; Soares, Daniel Candido Da Costa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Mackerel (Rastrelliger sp.) is a food fish in Indonesian waters, one of which is in the Ombai Strait, Atapupu waters. Mackerel has a high ome 3 content, high protein, delicious taste, and affordable price. However, attention is needed to the quality and quality of mackerel from the threat of parasites that can cause disease. Especially fish parasites found in the mouths of mackerel fish. This research was conducted to determine the number of parasite microhabitats, intensity, prevalence, and the relationship between fish length and body weight and the parasites obtained. The research sample was obtained from TPI Atapupu which was carried out from November 2023 to December 2023. The method used during the research was quantitative descriptive and the method used to take samples was random (random sampling). The total fish samples examined were 50 fish consisting of the species.